2019
DOI: 10.1155/2019/9240317
|View full text |Cite
|
Sign up to set email alerts
|

Multiperiod‐Ahead Wind Speed Forecasting Using Deep Neural Architecture and Ensemble Learning

Abstract: Accurate forecasting of wind speed plays a fundamental role in enabling reliable operation and planning for large-scale integration of wind turbines. It is difficult to obtain the accurate wind speed forecasting (WSF) due to the intermittent and random nature of wind energy. In this paper, a multiperiod-ahead WSF model based on the analysis of variance, stacked denoising autoencoder (SDAE), and ensemble learning is proposed. The analysis of variance classifies the training samples into different categories. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…The results for this hybrid model are then compared with ARIMA, Back propagation neural network (BPNN) and Generalized regression neural network (GRNN). Chen et al explored deep learning and ensemble methods for multi‐step wind speed forecasting for a wind farm site in China 33 Wind speed time‐series with time intervals of 15‐minutes, 1 hour, 4 hours, 8 hours, and 24 hours for a duration of six months is taken. Stacked denoising autoencoder (SDAE) based feature extraction technique is employed in tandem with deep learning model like LSTM to predict wind speed.…”
Section: Introductionmentioning
confidence: 99%
“…The results for this hybrid model are then compared with ARIMA, Back propagation neural network (BPNN) and Generalized regression neural network (GRNN). Chen et al explored deep learning and ensemble methods for multi‐step wind speed forecasting for a wind farm site in China 33 Wind speed time‐series with time intervals of 15‐minutes, 1 hour, 4 hours, 8 hours, and 24 hours for a duration of six months is taken. Stacked denoising autoencoder (SDAE) based feature extraction technique is employed in tandem with deep learning model like LSTM to predict wind speed.…”
Section: Introductionmentioning
confidence: 99%
“…Since wind speed largely determines the amount of electricity generated by a turbine, accurate prediction can provide a reliable and secure source for the production of wind energy and also decrease the operating cost of the power system [3,5]. This also helps the power system to adapt the dispatch schedule in time according to changes in the input of wind power, ensures the quality of power, and reduces the cost of maintaining the service [6].…”
Section: Introductionmentioning
confidence: 99%
“…Back propagation and support vector machine methods and their hybrids with empirical mode decomposition and wavelet transform, and an ensemble of the methods were used to predict wind speed in [30] and found that ensemble approaches predict better than the individual methods. A method which used analysis of variance to classify wind data into different categories, used stacked de-noising auto-encoder for training the classi ed data and nally used extreme learning machine to ne-tune and forecast from the trained model was proposed in [31]. Their method predicted better than the adaptive neuron-fuzzy inference system.…”
Section: Introductionmentioning
confidence: 99%